High-Density Single Nucleotide Polymorphisms Genetic Map Construction and Quantitative Trait Locus Mapping of Color-Related Traits of Purple Sweet Potato [Ipomoea batatas (L.) Lam.] - Yan, Hui; Ma, Meng; Ahmad, Muhammad Qadir; Arisha, Mohamed Hamed; Tang, Wei; Li, Chen; Zhang, Yungang; Kou, Meng; Wang, Xin; Gao, Runfei; Song, Weihan; Li, Zongyun; et al. (Frontiers in Plant Science, 2022)
Flesh color (FC), skin color (SC) and anthocyanin content (AC) are three important traits being used for commodity evaluation in purple fleshed sweetpotato. However, to date only few reports are available on the inheritance of these traits. In this study, we used a biparental mapping population of 274 F1 progeny generated from a cross between a dark purple-fleshed (‘Xuzishu 8’) and white-fleshed (‘Meiguohong’) sweetpotato variety for genetic analyses. Correlation analysis showed a significant positive correlation between AC, SC and FC. Medium to high heritability was observed for these traits. We detected single nucleotide polymorphisms (SNPs) by specific length amplified fragment sequencing (SLAF-seq) with the average sequencing depth of 51.72 and 25.76 for parents and progeny, respectively. Then we constructed an integrated genetic map consisting of 15 linkage groups (LG) of sweetpotato spanning on 2,233.66 cM with an average map distance of 0.71 cM between adjacent markers. Based on the linkage map, ten major quantitative trait loci (QTLs) associated to FC, SC and AC were identified on LG12 between 0 to 64.97 cM distance, including one QTL for SC and FC respectively, which explained 36.3 % and 45.9 % of phenotypic variation; eight QTLs for AC, which explained 10.5 % to 28.5 % of the variation. These major QTLs were highly consistent and co-localized on LG12. Positive correlation, high heritability and co-localization of QTLs on the same LG group confirms the significance of this study to establish a marker assisted breeding program for sweetpotato improvement.